Grafting of styrene and acrylic monomers onto polybutadiene - Del Valle, Yesid; Rivas, Luis; Méndez, Bernardo; Oliva, Haydee (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Isothermal free radical copolymetization of acrylic monomers and styrene in the presence of polybutadiene (PB), in solution, using tert-butylperoctoate (TBPO) as initiator were investigated. The acrylic monomers used were: methyI methacrylate (MMA), ethyl acrylate (EA) and n-butyl methacrylate (BMA). Preliminary tests with acrylic monomers and rubber were carried out to establish the time of styrene addition. Also, two leveIs of concentration for each acrylic monomer were investigated in order to study its effect on the reaction rate and the grafting efficiency. “Terpolymerizations” were made adding styrene to obtained elastomeric copolymers. For all the reactions, the evolution of the global conversion was determined gravimetrically. These results were compared with those obtained by 13C NMR spectra for copolymers and elastomeric terpolymers. The order of the monomer reactivities in the polymerization in the presence of polybutadien was: MMA> BMA > EA. A composition between 50 and 60% in the poly (butadiene-g-acrylic monomer) copolymer was established like point for addition of styrene. The influence of the polybutadiene like a delaying agent of the reaction of acrylic monomers was verified. The terpolymerizations reaction rates with different relations acrylic monomer / styrene showed a linear behavior, similar to the styrene one, independently of acrylic monomer and of feed comonomers relationship used. The 13C NMR spectra of the terpolymerizations samples with BMA displayed the signals corresponding to each monomer, indicating that is possible the formation of the terpolymer.